Recent Publications (Quarterly Journal of Economics, 1950)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 64, Issue 3, August 1950, Pages 491–494, https://doi.org/10.1093/qje/64.3.491 Published: 01 August 1950